Peranan Negara dalam Liberalisasi Ekonomi Vietnam: Analisis Terhadap Dasar Doi Moi 1986: The Role of the State in the Economic Liberalisation of Vietnam: An Analysis of the Doi Moi Policy 1986 - Sabtu, Muhamad Helmy; Mohamad Suhaimy, Khairul Azman; Razali, Nurul Aimi (Advances in Humanities and Contemporary Studies, 2020)
This article analyses the role of state in the policy of economic liberalisation in Vietnam. Doi Moi, which was launched in 1986, is a very influential and effective policy in changing the socio-economic landscape of the people in the country. The results of this study prove that there are positive effects on the increase of foreign investment inflows, the eradication of starvation and unruly poverty, the increase of level of education, the improvement of gender equality and women's rights as well as the sustainability of the environment after Doi Moi is implemented. Through Doi Moi, Vietnam is moving towards a developing country status with good economic performance both at the Southeast Asian and global.